Science, faith and the climate crisis - Myers, Sally; Hemstock, Sarah; Hanna, Edward (Emerald points., 2020)
Inspired by a 2019 conference, Moana Water of Life, and including real-life insights from a diverse range of participants, this book showcases the potential fruits of open dialogue between stakeholders to navigate the critical challenges to planetary health caused by the climate crisis. The Earth's climate is changing faster than at any point in the history of modern civilisation through human-induced global warming, yet public reactions to this scientific truth remain dissonant. Inspired by a 2019 conference, Moana Water of Life, this book showcases the challenges and potential fruits of an open dialogue between stakeholders to navigate the critical challenges to planetary health caused by the climate crisis. Inviting participants to contribute 'in their own voices', this book cuts across real-life insights, ranging from researchers from the Pacific Islands Region on the front line of devastating water surpluses and shortages, to the thoughts of leading climate change and Earth scientists, social scientists, educators, faith leaders, theologians and activists who are offering practical solutions to the problem. By highlighting this collection of inspiring stories at the local and global levels, the authors offer a vision of hope for communities in the future to communicate, adapt to change and ultimately resist further deterioration of the planet's health. All royalties from this book are being donated to the Red Cross in the Pacific Island Region.